The COVID-19 Pandemic – A Diagnostic Industry Perspective - Das, Shubhagata; Dunbar, Sherry (Frontiers in Cellular and Infection Microbiology, 2022)
The COVID-19 pandemic has brought about unprecedented changes to all facets of the healthcare system, including the diagnostic industry. The pandemic has highlighted both the challenges and strengths of the industry and has also provided valuable insights on how to be better prepared for future pandemics. In this perspective article, we describe the challenges faced by the diagnostic industry in general, particularly the difficulties encountered by Luminex Corporation, a diagnostic assay development and manufacturing company located in Austin, Texas, USA, as well as the mitigation strategies employed. In addition to discussion of the key challenges, the article provides insights on the lessons learned and steps that can be undertaken to better prepare for future outbreaks.